Use of the health belief model to explain perceptions of zoonotic disease risk by animal owners - Wheeler, Karen L., author; Trumbo, Craig, advisor; O'Keefe, Garrett, committee member; Morley, Paul, committee member (Colorado State University. Libraries, 2011)
The rise in the number of public health risks from zoonotic disease in just the past two decades has underscored both the importance of educating the public about risky health behaviors and preventive measures, and the need to communicate these topics in clear, concise and accessible language without inciting fear. People love their animals, typically sharing physical gestures of affection similar to those exchanged between humans. Most pet owners are poorly informed about risks posed by infectious agents that can be shared between animals and humans, and which pose a public health risk. To effectively communicate this information, we must first understand the determinants of a particular behavior: the role of beliefs, perception of risk, benefits, and barriers to change. The Health Belief Model, a theory that incorporates each of these factors, allows researchers to assess what might constitute a cue to action for individuals to make recommended changes in preventive health behavior. For this study examining the knowledge and perceptions of zoonotic disease risk and information-seeking behavior amongst small and mixed animal owners in the Inter-Mountain West, one thousand names were randomly selected from the client lists of the James L. Voss Veterinary Teaching Hospital at Colorado State University. Four hundred participants (40 percent) responded to a mailed, self-administered, anonymous survey. Descriptive analysis assessed awareness of two zoonotic diseases: Salmonella and Methicillin-resistant Staphylococcus aureus; and information-seeking behaviors related to animal health and disease risk. Analysis revealed that, adopting protective behaviors is best achieved by perceiving greater benefits to adopting the recommended behavior, perceiving fewer barriers, and receiving more cues to action. Results also found differences between small and mixed animal owners in several areas of inquiry, including knowledge of disease, perception of risk, perception of cues to action and in information-seeking behaviors.
Keywords: communication; health belief model; public health; risk perception; veterinary medicine; zoonotic disease